1998
DOI: 10.1161/01.hyp.32.6.972
|View full text |Cite|
|
Sign up to set email alerts
|

Inverse Relationship Between Fenfluramine-Induced Prolactin Release and Blood Pressure in Humans

Abstract: Abstract-Although substantial evidence from experimental animals suggests that augmentation and reduction in serotonergic neurotransmission both affect arterial blood pressure (BP), it is unknown whether "tonic" central serotonergic activity is related to resting BP variability in humans. We tested this hypothesis in a community sample by evaluating the relationship between resting BP and a neuropharmacologic index of brain serotonergic activity (the fenfluramine challenge test). Subjects were 270 generally he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 22 publications
2
17
0
Order By: Relevance
“…Results of this study noted a significantly inversely correlation between PRL and the age in whole study population, this finding agree with many studies which found an association between PRL secretion and the age [48,49].…”
Section: Discussionsupporting
confidence: 93%
“…Results of this study noted a significantly inversely correlation between PRL and the age in whole study population, this finding agree with many studies which found an association between PRL secretion and the age [48,49].…”
Section: Discussionsupporting
confidence: 93%
“…The association between the reduction of the brain 5-HTergic transmission and hypertension was performed in an article, which investigated if the tonic 5-HTergic activity is related to the variability of rest blood pressure in human beings (Muldoon et al 1998). To evaluate the brain 5-HTergic activity the authors used a neuroendocrine approach, which determined the prolactin secretory capacity through the fenfluramine administration, a 5-HT releaser.…”
Section: Hypertensionmentioning
confidence: 99%
“…Baseline age was modeled by dummy-coded variables for ages 48,54, and 60 years, with an age of 42 years as the reference category.…”
Section: Agementioning
confidence: 99%